The Legionella pneumophila replication vacuole: making a cozy niche inside host cells - Isberg, Ralph R. (2008)
The pathogenesis of Legionella pneumophila results from growth of the bacterium within lung macrophages after aerosols are inhaled from contaminated water sources. Interest in this microorganism stems from its ability to manipulate host cell vesicular trafficking pathways and to establish a membrane-bound replication vacuole, making it a model for intravacuolar pathogens. Establishment of the replication compartment requires a specialized translocation system that transports a large cadre of protein substrates across the vacuolar membrane. These substrates regulate vesicle traffic and survival pathways in the host cell. This review focuses on the strategies that L. pneumophila uses to establish intracellular growth and evaluates why the microorganism has accumulated an unprecedented number of translocated substrates targeted at host cells.